Custom centrifugal pump performance in supplying high viscos liquid - N. H. K., Anuar; Mohd Nizar, Mhd Razali; Mohamad Rusydi, Mohamad Yasin; Musfirah, Abdul Hadi; Abdul Nasir, Abd Ghafar (Penerbit UMP, 2021)
Viscosity is one of the factors affecting the performance of the centrifugal pump. A centrifugal pump is a device that used a driven motor called impeller to move fluid by rotational mechanism. This study is about the performance of a custom centrifugal pump when transferring viscous liquids. The main aim is to design and fabricate a device that can pump liquid with various viscosity using centrifugal pump. Liquids used in the experiment are comprised of a mixture of detergent and water with a different ratio to alter the viscosity. The viscosity is being identified by the usage of Zahn Cup Method with the temperature kept constant at 26°C throughout the experiment. Performance of the centrifugal pump is being investigated by four parameters which are the flow-rate, Total Dynamic Head (TDH), power and efficiency. Performance of the centrifugal pump can be accessed by altering the pump shaft speed in order to get various reading for the flow rate. In order to alter the pump shaft speed, the usage of the motor with Variable Frequency Drive (VFD) is implemented. The values for the flow-rate and pump shaft power are measured by flowmeter and Variable Frequency Drive (VFD). The Total Dynamic Head (TDH), hydraulic power and pump efficiency is calculated based on the reading of the flowmeter and pump shaft power displayed at Variable Frequency Drive (VFD). At the end of this project, the pump performance while pumping different viscous liquids at different flow rates is being identified.